Modelling and optimization of Searaser wave energy converter based hydroelectric power generation for Saint Martin's Island in Bangladesh - Shahriar, Tanvir; Habib, M. Ahsan; Hasanuzzaman, Md.; Shahrear-Bin-Zaman, M. (Elsevier, 2019)
Saint Martin's Island is one of the most notable tourist spots and the only coral island of Bangladesh in the Bay-of-Bengal. Yet due to lack of electricity supply, this beautiful island is becoming uninhabitable and losing tourist attraction. In this study, a decentralized Mini Hydroelectric Power Plant (MHPP) has been proposed and designed to mitigate electricity demand in the tourist resorts of the island during peak demand–hours: the energy input to the plant is supplied by harnessing ocean wave-power available in the coastal regions of the island with a novel and simple Wave Energy Converter (WEC) named Searaser. To decide about the installed capacity of the proposed MHPP, a field survey was conducted on the resorts of St. Martin's Island. The performance of Searaser in the context of the island was investigated theoretically which indicated that the Searaser is capable of producing about 35 m of water-head by utilizing the available wave-power. Realizing the availability of wave-power and adopting sustainable tourism policy, the estimated plant capacity was about 144 kW. This study remarks that the implementation of Searaser based MHPP technology in the St. Martin's Island can be a profitable and eco-friendly replacement of the existing stand-alone diesel-generators; it was also found that huge amount of Greenhouse Gas (GHG) emission can be prevented, and thereby the tourism potential can be enhanced as well. © 2019 Elsevier Ltd